Effect of Nano‐Sized Y2O3 Doping on the Electrical Properties of (Ba0.90Ca0.10)(Ti0.9Sn0.1)O3 Ceramics. Issue 3 (7th December 2017) - Chen, Zhi‐hui; Li, Zhi‐wei; Qiu, Jian‐hua; Zhao, Tian‐xiang; Zhu, Ke‐qin; Ding, Jian‐ning; Zhu, Wei‐qin; Xu, Jiu‐jun
Abstract : Well dispersed Y2 O3 nanoparticles are prepared by azeotropic co‐precipitation method. (Ba0.90 Ca0.10 )(Ti0.9 Sn0.1 )O3 lead‐free piezoelectric ceramics doped with the nano‐sized Y2 O3 (BCTZY, x  = 0.01–0.09%) are synthesized at 1460 °C for 2 h via solid‐state sintering method. X‐ray diffraction suggests typical perovskite structure of all the compositions. The addition of the nano‐Y2 O3 results in the improvement in dielectric and piezoelectric properties. The optimized piezoelectric properties is obtained at x  = 0.01 with d33 of 596 pC/N and Kp of 57.1%, respectively. Abstract : Nano sized Y2 O3 powders can be prepared by azeotropic co‐precipitation method. Doping with Y2 O3 nanoparticles in (Ba, Ca)(Ti, Sn)O3 piezoelectric ceramics is effective to improved the electric properties.